2015
DOI: 10.1161/circulationaha.115.015951
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Free-Wall Rupture by Left Ventricular Angiogram After Inferior ST-Segment–Elevation Myocardial Infarction

Abstract: A 67-year-old man with type 2 diabetes mellitus presented after an out-of-hospital cardiac arrest with pulseless electric activity (PEA) preceded by significant chest discomfort and syncope. Cardiopulmonary resuscitation was started for PEA arrest with return of spontaneous circulation after 20 minutes. His initial ECG showed an acute inferior ST-segmentelevation myocardial infarction (STEMI; Figure 1). In the emergency department, he experienced another PEA arrest and an ECG showed evidence of a moderate peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…LVG may detect contrast extravasations not detected by transthoracic echocardiography as a pericardial effusion. Reddy et al too reported an inferior wall rupture detected by LVG, not transthoracic echocardiography [2]. The view angle is important in such cases.…”
Section: Discussionmentioning
confidence: 96%
“…LVG may detect contrast extravasations not detected by transthoracic echocardiography as a pericardial effusion. Reddy et al too reported an inferior wall rupture detected by LVG, not transthoracic echocardiography [2]. The view angle is important in such cases.…”
Section: Discussionmentioning
confidence: 96%
“…Its prevalence has been greatly influenced by myocardial reperfusion therapies, going from values between 6% and 8% in the 1970s and 1980s to a rate of less than 1% today. 5,6 Early diagnosis is essential for a better clinical outcome, but this does not always guarantee a favorable outcome, since open surgical treatment must be performed in a hemodynamically unstable patient.…”
Section: Discussionmentioning
confidence: 99%
“…Free wall rupture is one of the major complications of myocardial infarction [6]. The incidence of ST-elevation myocardial infarction (STEMI) varies from 0.8% to 6.2%, usually within four days after the infarction [7]. Left ventricular rupture is more common but some cases of right ventricular rupture have been described [8].…”
Section: Types Of Mechanical Complications Of Amimentioning
confidence: 99%